AMPK inhibits Smad3‐mediated autoinduction of TGF‐β1 in gastric cancer cells. Issue 6 (3rd February 2021) - Zou, Junrong; Li, Cong; Jiang, Shanshan; Luo, Lingyu; Yan, Xiaohua; Huang, Deqiang; Luo, Zhijun
Abstract: We have previously shown that adenine monophosphate‐activated protein kinase (AMPK) regulates transforming growth factor β (TGF‐β)‐triggered Smad3 phosphorylation. Here we report that AMPK inhibits TGF‐β1 production. First, metformin reduced mRNA levels of TGF‐β1 in gastric cancer cells, in parallel to the decrease of its protein abundance. The effects were more prominent in the cells containing LKB1, an upstream kinase of AMPK. Second, knockdown of Smad3 by siRNA abrogated the expression of TGF‐β1. Third, metformin suppressed firefly luciferase activity whose transcription was driven by TGF‐β1 promoter. In accordance, deletion of the putative binding site of Smad3 in the TGF‐β1 promoter region severely impaired the promoter activity and response to metformin. Fourth, in support of our in vitro study, clinical treatment of type 2 diabetes with metformin significantly reduced the plasma level of TGF‐β1. Finally, immunohistochemical studies revealed that TGF‐β1 was highly expressed in human gastric cancer tissues as compared with adjacent normal tissues. In contrast, p‐AMPK exhibited opposite changes. Furthermore, the survival rate of gastric cancer patients was positively correlated with p‐AMPK and negative with TGF‐β1. Therefore, our present studies depict a mechanism underlying AMPK suppression of TGF‐β1 autoinduction, which is mediated through inhibition of Smad3 phosphorylation and activation. Collectively, our study sheds a light on the potential usage of AMPK activators in the treatment of TGF‐β1‐mediated gastric cancer progression.